2015
DOI: 10.14814/phy2.12331
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency aggravates ischemic acute kidney injury in rats

Abstract: Vitamin D deficiency (VDD) increases the risk of death in hospitalized patients. Renal ischemia/reperfusion injury (IRI) induces acute kidney injury (AKI), which activates cell cycle inhibitors, including p21, a cyclin-dependent kinase inhibitor and genomic target of 25-hydroxyvitamin D, which is in turn a potent immunomodulator with antiproliferative effects. In this study, we assess the impact of VDD in renal IRI. Wistar rats were divided into groups, each evaluated for 30 days: control (receiving a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 46 publications
3
39
0
7
Order By: Relevance
“…125,126 In animal models, pre-administration of 1,25D attenuated AKI resulting from a variety of nephrotoxic insults, including ischemia-reperfusion injury, [127][128][129] gentamicin, 130 cyclosporine, 131 cisplatin, 132 glomerulonephritis, 133 and obstruction. 134 Furthermore, de Braganca et al 135 investigated the effects of dietary-induced 25D deficiency on the severity of AKI in rats. They found that rats fed a vitamin D−free diet had a more severe decrease in glomerular filtration rate, greater urinary protein excretion, and increased tubular necrosis after ischemia-reperfusion injury compared with rats fed a standard diet.…”
Section: Vitamin D Metabolites As Novel Therapies In Aki and Criticalmentioning
confidence: 99%
“…125,126 In animal models, pre-administration of 1,25D attenuated AKI resulting from a variety of nephrotoxic insults, including ischemia-reperfusion injury, [127][128][129] gentamicin, 130 cyclosporine, 131 cisplatin, 132 glomerulonephritis, 133 and obstruction. 134 Furthermore, de Braganca et al 135 investigated the effects of dietary-induced 25D deficiency on the severity of AKI in rats. They found that rats fed a vitamin D−free diet had a more severe decrease in glomerular filtration rate, greater urinary protein excretion, and increased tubular necrosis after ischemia-reperfusion injury compared with rats fed a standard diet.…”
Section: Vitamin D Metabolites As Novel Therapies In Aki and Criticalmentioning
confidence: 99%
“…VD may also modulate oxidative stress and inflammation, reducing fibroblast activation and interstitial inflammation [74,75,77,109] Moreover, CKD progression and lower expression of megalin have been associated with lower 25(OH)-VD reuptake and therefore reducing intracrine 1,25(OH) 2 -VD production in the renal proximal tubules (Figure 2b) [50,51,110]. On the other hand, increasing levels of proteinuria may perpetuate VDD.…”
Section: Vd and Ckd: Human Studiesmentioning
confidence: 99%
“…Thus, low levels of vitamin D can be deleterious and impair the recovery of renal diseases and/or even accelerate the progression of renal disease. In a previous study, we showed that vitamin D deficiency exerted a pivotal role on the aggravation of acute kidney injury (AKI) after ischemia/reperfusion (I/R) insult ( 9 ). We also demonstrated that vitamin D deficiency favored renal capillary rarefaction, and increased renal fibrosis and inflammation ( 10 ).…”
Section: Introductionmentioning
confidence: 99%